(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The aim of the research is to define external auditing and clarify its conceptual framework in relation to the importance and steps of performance control. It also aims to define the concept of banking performance evaluation and the initiative of the Central Bank of Iraq, as well as explain the role of external auditing in evaluating the performance of specialized banks in implementing the Central Bank of Iraq’s initiative as a developmental program. The researchers relied on a set of tools to achieve the objectives of the current research, including examining financial data, analytical procedures, and selecting key performance indicators to effectively evaluate the performance of specialized banks in implementing the Central Bank of Iraq’s initiative. The research community included public banks operating in Iraq, while the research sample specifically focused on the agricultural bank. The research reached several conclusions, the most important of which was the existence of shortcomings in the implementation of the Central Bank of Iraq’s initiative by the bank. The percentage of agricultural loans granted through the Central Bank of Iraq’s initiative accounted for only 2.70% of the total allocated amount for the bank, starting from the launch of the initiative until the year 2020. This represents a low percentage, indicating weakness in granting loans related to the Central Bank’s initiative. The research recommended a number of recommendations, including the necessity of activating the necessary means through raising awareness among the public and those interested about the objectives of the Central Bank of Iraq’s initiative, in order to attract farmers and those involved in the agricultural sector to borrow and enhance the country’s agricultural reality, reduce agricultural imports, and rely on local agricultural production.